Management of Massive Pulmonary Hemorrhage Following Pulmonary Endarterectomy - Yıldızeli, Bedrettin; Arslan, Özgür; Taş, Serpil; Eldem, Barkın; Aksoy, Eray; Koçak, Tuncer; Sunar, Hasan (The Thoracic and Cardiovascular Surgeon, 2014)
Massive pulmonary hemorrhage is a potentially fatal complication of pulmonary endarterectomy. We describe a successful management in which the patient's right lower lobe bronchus was occluded with a Fogarty balloon catheter while on peripheral venoarterial extracorporeal membrane oxygenation.
Keywords: pulmonary endarterectomy; extracorporeal membrane oxygenation; postoperative care